KONSEP HUBUNGAN HUKUM INTERNASIONAL DAN HUKUM NEGARA DENGAN ADANYA PRIMAT SEBAGAI KONSTRUKSI HUKUM - Nurussyifa, Nurussyifa; Putri, Zaskia Alya; Maturidi, Restu; Anggraini, Sherly; Zaqila, Avivah Zhia; Guspita, Devika Rosa (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2026)
The examination of the position and relationship between international legal order and the domestic legal system of a state represents one of the most foundational discussions in international legal scholarship. The central inquiry is whether these two normative orders exist independently of one another, or whether they merge into a single hierarchical system of norms. This study aims to analyze the concept of primacy—that is, the supremacy or dominance of one legal system over the other—as a legal construction that addresses this fundamental question. The research employs a normative juridical method, integrating conceptual, historical, and comparative legal approaches. The findings reveal that both the primacy of international law and the primacy of national law rest upon strong argumentative foundations, yet each harbors significant limitations when applied in absolute terms. In practice, states tend to adopt a pragmatic-coordinative approach that accommodates the interests of both systems in a balanced manner. Indonesia, as a state with an open and dynamic legal system, applies a flexible transformation mechanism to integrate international norms into its domestic legal order—an approach that warrants strengthening through regulatory framework reform